THE APPLICATION OF COMMUNITY RESEARCH IN DETERMINING THE INITIAL STAGE OF COACHING PROGRAMME AT CLASS IIA KARAWANG PRISON - Azazuhri, Muhamad Reza; Biafri, Vivi Sylviani; Aulia, Qistina (Universitas Nusa Cendana, 2025)
The study titled The Application of Community Research in Determining the Initial Stage of Coaching Program at Class IIA Karawang Prison investigates the challenges faced in implementing the Initial Stage Development Litmas. The primary aim is to evaluate the human resource limitations and communication barriers between relevant institutions that hinder effective prisoner rehabilitation. Utilizing qualitative research methods, the study highlights the inadequacy of community supervisors at the Bekasi Probation and Parole Office, leading to a focus on Reintegration Litmas instead of comprehensive developmental support. Findings reveal significant gaps in assessing prisoners' needs, affecting the overall effectiveness of the correctional system. Additionally, the study emphasizes the importance of inter-institutional cooperation and suggests innovative solutions, such as the Community Supervisor Helper program, to address staffing shortages. Ultimately, a coordinated and structured approach is essential for optimizing rehabilitation efforts at Karawang Class IIA Prison. Keywords: Rehabilitation; Community Research; Inter-institutional Cooperation